SOME ASPECTS OF TEST VALIDITY IN THE CZECH MILITARY - Šikolová, Mária; Koláčková, Ludmila (PEOPLE: International Journal of Social Sciences, 2017)
The language exams in the Czech military are undoubtedly high-stakes tests, and their results affect the lives of thousands of military professionals. As a consequence of their importance, the quality of the exams is often questioned, leading to a need for continual monitoring and improvement. Test validity should not be solely the domain of testers, but teachers, as well as candidates, should a voice in the process as well. This concern is why one of the research objectives is to uncover how the exam is perceived by candidates. The instrument for gathering the data is a questionnaire developed by the authors and distributed to uncover the candidates’ opinions on the exam, both as a whole and in particular parts. Teachers’ views on the tests constitute another piece of evidence of test validity, and these are currently being gathered less formally, but will nonetheless be addressed accordingly. This contribution will illustrate the preliminary results of the data collected from the questionnaire for the exam candidates, as well as the results of a study dealing with a change in assessing testing writing based on the feedback from the teachers.